Experimental and theoretical studies on interaction of hybrid 'micro-flowers like structures on graphene - Rozalina, Z.; Law, K.C.; Yusoff, S.F.A.Z.; Lim, C.S. (2016)
We report experimentally and theoretical studies of formation in hybrid of silver (Ag),micro-flowers like structures' in graphene. An agglomeration silver nanoparticles were deposited on graphene surfaces using electrochemical deposition technique and thus formed the 'micro-flowers like structure'. The properties of these structures in interaction with graphene substrate will be explored in the meaning of localized surface plasmon resonance (LSPR). The deposition time was varied in order to control the sizes and shapes of deposited microstructures. The morphology of graphene surfaces these structures was observed using the Field Emission Scanning Electron Microscope (FESEM), Atomic Force Microscope (AFM) and surface profiler. Images from FESEM shows the structures increases with the deposition time. The presence of graphene and Ag composition con finned using Raman Spectroscopy and Energy Dispersive X-ray Spectroscopy (EDX). Raman spectra shows the intensity of LSPR generated was the highest at the sample with deposition time of l.5min. CST Microwave Studio has been used to simulate the absorption characteristics of the samples. Findings from simulation shows the intensity of LSPR increased with deposition time. It is also observed that the absorption peak was redshifted and broadened due to the increase of the structure size.